Mycobacterium tuberculosis Multidrug-Resistant Strain M Induces Low IL-8 and Inhibits TNF-α Secretion by Bronchial Epithelial Cells Altering Neutrophil Effector Functions - Denise Kviatcovsky; Leonardo Rivadeneyra; Luciana Balboa; Noemí Yokobori; Beatriz López; Viviana Ritacco; Mirta Schattner; María del Carmen Sasiain; Silvia de la Barrera (Hindawi Limited, 2017)
M strain, the most prevalent multidrug-resistant strain of Mycobacterium tuberculosis (Mtb) in Argentina, has mounted mechanisms to evade innate immune response. The role of human bronchial epithelium in Mtb infection remains unknown as well as its crosstalk with neutrophils (PMN). In this work, we evaluate whether M and H37Rv strains invade and replicate within bronchial epithelial cell line Calu-6 and how conditioned media (CM) derived from infected cells alter PMN responses. We demonstrated that M infects and survives within Calu-6 without promoting death. CM from M-infected Calu-6 (M-CM) did not attract PMN in correlation with its low IL-8 content compared to H37Rv-CM. Also, PMN activation and ROS production in response to irradiated H37Rv were impaired after treatment with M-CM due to the lack of TNF-α. Interestingly, M-CM increased H37Rv replication in PMN which would allow the spreading of mycobacteria upon PMN death and sustain IL-8 release. Thus, our results indicate that even at low invasion/replication rate within Calu-6, M induces the secretion of factors altering the crosstalk between these nonphagocytic cells and PMN, representing an evasion mechanism developed by M strain to persist in the host. These data provide new insights on the role of bronchial epithelium upon M infection.